An Exploration of How the Employee–Organization Relationship Affects the Linkage Between Perception of Developmental Human Resource Practices and Employee Outcomes* - Kuvaas, Bård (Journal of Management Studies, 2008)
abstract The purpose of the present study was to examine whether and how the quality of the employee–organization relationship (EOR) influences the relationship between employee perception of developmental human resource (HR) practices and employee outcomes. Analyses of 593 employees representing 64 local savings banks in Norway showed that four indicators of the EOR (perceived organizational support, affective organizational commitment, and procedural and interactional justice) moderated the relationship between perception of developmental HR practices and individual work performance. A strong and direct negative relationship was found between perception of developmental HR practices and turnover intention, but perceived procedural and interactional justice moderated this linkage. No support was found for a mediating role of the EOR indicators in the relationship between perception of developmental HR practices and employee outcomes. Implications and directions for future research are discussed.